Multimodal Imaging-Based Phenotyping of a Singaporean Hospital-Based Cohort of High Myopia Patients - Tey, Kai Yuan; Hoang, Quan V.; Loh, Isabella Q.; Dan, Yee Shan; Wong, Qiu Ying; Yu, Daryle Jason G.; Yandri, Vivi R.; Ang, Marcus; Cheung, Gemmy C. M.; Lee, Shu Yen; Wong, Tien Yin; , SNEC Retina Group; et al. (Frontiers in Medicine, 2022)
Purpose: To assess the effect of axial length (AL) on the prevalence of pathologic myopia (PM) and associated myopic features in a Singaporean hospital-based cohort of highly myopic (HM) patients. Methods: 923 HM eyes from 495 individuals were recruited from the Myopic and Pathologic Eyes in Singapore (MyoPES) cohort and underwent ocular biometry, fundus photography, fundus autofluorescence and swept-source optical coherence tomography. Images were analyzed for presence of myopic macular degeneration (MMD), myopic choroidal neovascularization (mCNV), myopic traction maculopathy (MTM), peripapillary atrophy (PPA), myopic tilted disc, posterior staphyloma (PS), dome-shaped macula (DSM), vitreomacular adhesions (VMA), and epiretinal membrane (ERM). Eyes were stratified into quartiles based on axial lengths to determine cut-off values to perform comparisons between shorter-length and longer-length groups. χ² test was done to determine the difference in the prevalence of pathologies between groups. Results: Overall, mean AL was 29.2 ± 2.2 mm (range 25.0 to 36.7 mm). MMD, PPA, myopic tilted disc, and ERM has AL threshold of AL ≥ 27.5 mm, whereas MTM has a AL threshold of ≥ 29.0 mm. We found that there was a significantly higher prevalence of MMD (88.2% vs. 49.4% ; p < 0.001), PPA (98.1% vs. 80.1%; p < 0.001), myopic tilted disc (72.7% vs. 50.2%; p < 0.001), and ERM (81.4% vs. 17.3%; p = 0.003) in eyes with AL ≥ 27.5 mm vs. eyes without AL < 27.5 mm. Prevalence of MTM (34.7% vs. 32.1%; p < 0.001), mCNV (17.4% vs. 12.1%; p = 0.03), PS (43.4% vs. 34.7%; p = 0.012), DSM (21.3% vs. 13.2%; p = 0.002, and VMA (5.9% vs. 2.6%; p = 0.014) in eyes with AL ≥ 29.0 mm compared with AL < 29. 0mm. Conclusion: Our study describes the overall prevalence of PM and related pathologies amongst HM patients in our hospital-based cohort. Longer eyes even amongst HM eyes had a significantly higher prevalence of PM-associated pathologies studied. This supports the premise that eyes with longer AL, even amongst HM eyes may be at greater risk of vision-threatening changes and therefore merit regular follow-up.